2023
DOI: 10.1097/pra.0000000000000678
|View full text |Cite
|
Sign up to set email alerts
|

Therapy Strategies for Late-life Depression: A Review

Abstract: Background: Depression in the elderly requires different treatment options because therapies that are commonly used for depression in younger patients show different effects later in life. Treatment options for late-life depression (LLD) are summarized in this article. Methods: A literature search in Medline/ PubMed performed in June 2020 identified 83 relevant studies. Results: Pharmacotherapy with selective serotonin reuptake inhibitors can be an effective first-line treatment in LLD, but > 50% of elderly pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 88 publications
(359 reference statements)
0
5
0
Order By: Relevance
“…Most evidence suggests that pharmacological and psychological treatments are more effective in patients with LLD, which may be related to improvements in their overall physical functioning during treatment. However, LLD has a poorer prognosis, and its treatment is more challenging than that in young adults, with a higher incidence of comorbidities and adverse events due to the use of multiple medications ( Piel and Quante, 2023 ); therefore, it is essential to individualize treatment regimens for different individuals. Additionally, the development of effective and low-cost preventive measures for the majority of older adults remains a major challenge in the prevention of LLD ( Vyas and Okereke, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most evidence suggests that pharmacological and psychological treatments are more effective in patients with LLD, which may be related to improvements in their overall physical functioning during treatment. However, LLD has a poorer prognosis, and its treatment is more challenging than that in young adults, with a higher incidence of comorbidities and adverse events due to the use of multiple medications ( Piel and Quante, 2023 ); therefore, it is essential to individualize treatment regimens for different individuals. Additionally, the development of effective and low-cost preventive measures for the majority of older adults remains a major challenge in the prevention of LLD ( Vyas and Okereke, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, addressing a higher demand for mental health care among older adults in Chile, and improving the ability to detect and treat mental health problems in this age group, should be a priority. According to previous research, psychotherapy can be an effective strategy to treat common mental disorders in old age [ 15 17 ], even more effective compared to other age groups [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The existing evidence has shown that psychotherapy can be effective to treat depression among older adults [ 15 17 ]. Although Cuijpers et al [ 16 ] findings did not support a greater efficacy of psychotherapy for depression among older adults, compared to younger adults, a recent study in England found that psychotherapy was more effective to reach recovery from depression and anxiety among older adults, compared to working age adults [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…When depressed older adults do receive treatment, antidepressants remain one of the most common first-line measures, and all three kinds of antidepressants (TCAs, SSRIs, MAOIs) are generally effective and tolerated by older patients (Bottino et al, 2012). However, many patients do not respond to antidepressants at all (Gutsmiedl et al, 2020;Mallery et al, 2019) or see only limited benefits and no remission (Piel & Quante, 2023). Several factors specific to older adults may contribute to their treatment resistance, including comorbid medical conditions, functional changes in the brain during aging, poor adherence to treatment due to memory/cognitive decline, changes in drug metabolism, and suboptimal prescription of antidepressants (Lenze et al, 2008;Kok & Reynolds, 2017).…”
Section: Treatmentmentioning
confidence: 99%